Reduced Aortic Distensibility is Associated With Higher Aorto‐Carotid Wave Transmission and Central Aortic Systolic Pressure in Young Adults After Coarctation Repair. Issue 7 (2nd April 2019) - Kowalski, Remi; Lee, Melissa G. Y.; Doyle, Lex W.; Cheong, Jeanie L. Y.; Smolich, Joseph J.; d'Udekem, Yves; Mynard, Jonathan P.; Cheung, Michael M. H.
Abstract : Background: The long‐term prognosis of patients with repaired aortic coarctation is characterized by high rates of cardiovascular and cerebrovascular disease related to hypertension, the basis of which remains unclear. To define potential underlying mechanisms, we investigated aortic and carotid arterial biomechanics and wave dynamics, and determinants of aortic systolic blood pressure, in young adults after coarctation repair. Methods and Results: Aortic arch and carotid biomechanics, wave intensity and wave power, and central aortic blood pressure, were derived from echocardiography and brachial blood pressure in 43 young adults after coarctation repair and 42 controls. Coarctation subjects had higher brachial and central systolic blood pressure ( P =0.04), while aortic compliance was lower and characteristic impedance (Zc ) higher. Although carotid intima‐media thickness was higher ( P <0.001), carotid biomechanics were no different. Carotid forward compression wave power was higher and was negatively correlated with aortic compliance ( R 2 =0.42, P <0.001) and distensibility ( R 2 =0.37, P =0.001) in coarctation subjects. Aortic wave power and wave reflection indices were no different in control and coarctation patients, but coarctation patients with elevated aortic Zc had greater aorto‐carotid transmission of forward compression wave power ( P =0.006). Aortic distensibility was the only independent predictor of central aortic systolic blood pressure on multivariable analysis. Conclusions: Young adults following coarctation repair had a less compliant aorta, but no change in carotid biomechanics. Reduced aortic distensibility was related to greater transmission of aortic forward wave energy into the carotid artery and higher central aortic systolic blood pressure. These findings suggest that reduced aortic distensibility may contribute to later cardiovascular and cerebrovascular disease after coarctation repair.